Strategi Dakwah NU Berbasis Kultural Dan Muhammadiyah Berbasis Purifikasi: Studi Komparatif - Musdalifa; Kamal Yusuf; Ahmad Fajar Habibullah (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
Da'wah plays a central role in the process of spreading and developing Islam in Indonesia. The two largest Islamic organizations in the country, namely Nahdlatul Ulama (NU) and Muhammadiyah, show different styles of da'wah approaches in principle. Nahdlatul Ulama (NU) adopts a cultural-based da'wah model, which accommodates Islamic values into local traditions, while Muhammadiyah carries a purification-based da'wah approach, which focuses on purifying Islamic teachings in accordance with the principles of the Qur'an and Hadith. Although these methodological differences have been widely researched, there is still a void of in-depth studies on the effectiveness and impact of these two approaches in the context of modern society, especially in the face of the dynamics of globalization and digitalization. This study aims to find out the history of the birth of Nahdlatul Ulama (NU) and Muhammadiyah and comparatively examine the culturally-based da'wah strategy of Nahdlatul Ulama (NU) and purification-based Muhammadiyah. This study uses a descriptive qualitative research method with a comparative study approach. The results of this study reveal that Nahdlatul Ulama (NU) and Muhammadiyah have different da'wah approaches, with NU promoting cultural-based da'wah while Muhammadiyah emphasizes a purification approach. Both play an important role in building a religious and progressive society amid the challenges of globalization and digitalization in Indonesia.